Immunity and Fibrogenesis: The Role of Th17/IL-17 Axis in HBV and HCV-induced Chronic Hepatitis and Progression to Cirrhosis - Paquissi, Feliciano Chanana (Frontiers in Immunology, 2017)
Cirrhosis is a common final pathway for most chronic liver diseases; representing an increasing burden worldwide and is associated with increased morbidity and mortality. Current evidence has shown that, after an initial injury, the immune response has a significant participation in the ongoing damage, and progression from chronic viral hepatitis (CVH) to cirrhosis, driving the activation and maintenance of main fibrogenic pathways. Among immune deregulations, those related to Th17/IL-17 axis have been recognized as key immunopathological and prognostic elements in patients with CVH. The Th17/IL-17 axis has been found involved in several points of fibrogenesis chain from the activation of stellate cells, increased expression of profibrotic factors as TGF-β, promotion of the myofibroblastic or epithelial-mesenchymal transition, stimulation of the synthesis of collagen, and induction of imbalance between matrix metalloproteinases and tissue inhibitors of metalloproteinases (TIMPs). It also promotes the recruitment of inflammatory cells and increases the expression of proinflammatory cytokines like IL-6 and IL-23. So, the Th17/IL-17 axis is simultaneously the fuel and the flame of a sustained proinflammatory and profibrotic environment. This work aims to present the immunopathologic and prognostic role of the Th17/IL-17 axis and related pathways in fibrogenesis and progression to cirrhosis in patients with liver disease due to hepatitis B virus (HBV) and hepatitis C virus (HCV). Keywords: Th17. Interleukin-17. TGF-β. Fibrogenesis. Cirrhosis. Chronic Viral Hepatitis.